Metastasis-Associated Cell Surface Oncoproteomics - Karhemo, Piia-Riitta; Hyvönen, Maija; Laakkonen, Pirjo (Frontiers in Pharmacology, 2012)
Oncoproteomics aims to the discovery of molecular markers, drug targets and pathways by studying cancer specific protein expression, localization, modification and interaction. Cell surface proteins play a central role in several pathological conditions, including cancer and its metastatic spread. However, cell surface proteins are underrepresented in proteomics analyses performed from the whole cell extracts due to their hydrophobicity and low abundance. Different methods have been developed to enrich and isolate the cell surface proteins to reduce sample complexity. Despite the method selected, the primary difficulty encountered is the solubilization of the hydrophobic transmembrane proteins from the lipid bilayer. This review focuses on proteomic analyses of metastasis-associated proteins identified using the cell surface biotinylation method. Interestingly, also certain intracellular proteins were identified from the cell surface samples. The function of these proteins at the cell surface might well differ from their function inside the cell.